ranaazad wrote:

Vyshak wrote:

St1: G - 5 > H - 5 --> Clearly sufficient to prove G > H

St2: G(G - H) > 0 --> G > 0 or G > H

If G > 0; H can be 0 and G(G - H) > 0 --> In this case is G > H? No

Not Sufficient

Answer: A

Hi, thank you for your explanation. Here, the question asks whether G>H

In statement 2, the inequality clearly satisfies this condition. l am not clear why its still insufficient.

Help?

Hi,

I am not able to understand my own explanation for the 2nd statement. I will edit my solution.

Please refer to the below explanation for the 2nd statement:

G^2 - GH > 0

G^2 is positive --> G can be negative or positive

Suppose the value of GH is negative --> If G is positive and H is negative then G > H

If G is negative and H is positive then G < H

Not Sufficient